A contrastive analysis of modality between english and behdini-kurdish - Hasso, Yousra; Toma , Shivan (Humanities Journal of University of Zakho, 2023)
The current study intends to conduct a comparative analysis of modality in English and Behdini-Kurdish. Modality is a linguistic category pertaining to expressing possibility and necessity, among other meanings. The paper’s central problem is that Behdini-Kurdish learners face difficulty in comprehending the notion of modality in English, precisely of modal auxiliary verbs. The primary goals of this investigation are to define epistemic and deontic modalities in the two languages in order to illustrate the similarities and dissimilarities between them. The results reveal that modals in English are predominantly grammatical auxiliaries. In contrast, in Kurdish, they are mainly lexical items, many of which are used to represent a single English modal auxiliary. The findings of the study are summarized in a number of conclusions.